2023
DOI: 10.3390/microorganisms11030674
|View full text |Cite
|
Sign up to set email alerts
|

High Variation in Protist Diversity and Community Composition in Surface Sediment of Hot Springs in Himalayan Geothermal Belt, China

Abstract: Hot springs are some of the most special environments on Earth. Many prokaryotic and eukaryotic microbes have been found to live in this environment. The Himalayan geothermal belt (HGB) has numerous hot springs spread across the area. Comprehensive research using molecular techniques to investigate eukaryotic microorganisms is still lacking; investigating the composition and diversity of eukaryotic microorganisms such as protists in the hot spring ecosystems will not only provide critical information on the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In a study, high variation in microbial diversity was found in the hot springs of the Himalayan Geothermal Belt in China. The high variation in microbial diversity is ascribed to the different in environmental conditions (temperature, salinity, and pH) of these hot springs [47].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, high variation in microbial diversity was found in the hot springs of the Himalayan Geothermal Belt in China. The high variation in microbial diversity is ascribed to the different in environmental conditions (temperature, salinity, and pH) of these hot springs [47].…”
Section: Discussionmentioning
confidence: 99%
“…Idiosyncratic to the above community structure axiomatic for hydrothermal ecosystems, a geochemically unusual category of Trans-Himalayan hot springs (poor in total dissolved solids including silicon, but rich in boron, sodium and diverse sulfur species), located on the either side of the tectonically active Indus Tsangpo Suture Zone (ITSZ, the collision intersection between the Asian and Indian continental crusts engaged in Himalayan orogeny) in eastern Ladakh, India [13–16], have been reported to feature extra-ordinarily high habitability [5, 10, 17, 18]. Concurrent to such reports of exceedingly bio-diverse microbiomes from the springs of the Puga and Chumathang geothermal areas situated on the Changthang plateau in the south and north of the ITSZ respectively, studies of microbial diversity within the vent-waters, and vent-adjacent niches, of a number of hot springs located across discrete Himalayan and Trans-Himalayan geothermal regions have corroborated that hydrothermal environments were not “Thermophiles Only Territories” [1926].…”
Section: Introductionmentioning
confidence: 95%
“…Compared with other well studied hydrothermal systems, the geochemical specialty of these Trans-Himalayan hot springs lies in their paucity of dissolved solids in general and calcium and silicon in particular, which again is accompanied by the exceptional abundance of boron, chlorine, sodium, and various sulfur species including both sulfide and sulfate. Concurrent to such reports of highly bio-diverse microbiomes from the hot springs of the Puga valley and Chumathang geothermal areas situated on the Changthang plateau, to the south and north of the ITSZ respectively, studies of microbial diversity within the vent-waters, and vent-adjacent areas, of a number of hot springs located across discrete Himalayan and Trans-Himalayan geothermal regions have corroborated that hydrothermal environments are not “Thermophiles only” territories [1926].…”
Section: Introductionmentioning
confidence: 97%